The innovative company : an ill-defined object - e uthor; Borzillo, Stefano (London, UK : ISTE, Ltd. ; Hoboken, NJ : Wiley, 2017)
The concept of innovation is the result of human activities carried out to produce a new product, service or something new that creates value. More recently, the idea of an innovative enterprise, organization or company has emerged, thanks to an increasing interest in innovation as an essential process in a variety of economic, technological and sociological contexts. This book is part of a set on Innovation between Risk and Reward and focuses on the close relationship between innovation and knowledge. It provides the reader with the outline of an innovative company, focusing on the organizational aspects that contribute to defining it and sketching out the profile of what an innovative company is or should be in the age of knowledge. The authors explore the literary corpus in order to outline the state of the art but also the reality of innovative enterprise in the form of meetings and interviews with both large and small companies.
Evolution of the Concept of Innovation -- Innovation: A Knowledge-based Phenomenon -- Pivots of Innovation in the Age of Knowledge -- The Various Approaches to Innovation Adopted by Companies -- Organizational Levers -- Conclusion.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed July 26, 2017).
John Wiley and Sons
Keywords: Organizational change; Organizational Innovation; Changement organisationnel; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Organizational change